2000
DOI: 10.1046/j.1537-2995.2000.40111393.x
|View full text |Cite
|
Sign up to set email alerts
|

HCV lookback in the United States:effectiveness of an extended lookback program

Abstract: The yield of both programs was limited by the high percentage of recipients who had died. Pediatric recipients were more likely to be living at the time of notification. The incremental program was less efficacious than the FDA program in identifying newly HCV-positive recipients, but one-third of the newly detected HCV cases were identified through the incremental program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…In those studies, 41 to 71 percent of recipients of blood components targeted for lookback were found to be dead. However, the number of patients not traceable in our study (28%) was considerably higher than the data published in many studies, including one which was performed in the United States 9 . One explanation could be that at least some of the studies with better yields were performed in countries with socialized medicine or civil registration systems, such as Denmark and Canada, 5,7 where patients are more traceable.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In those studies, 41 to 71 percent of recipients of blood components targeted for lookback were found to be dead. However, the number of patients not traceable in our study (28%) was considerably higher than the data published in many studies, including one which was performed in the United States 9 . One explanation could be that at least some of the studies with better yields were performed in countries with socialized medicine or civil registration systems, such as Denmark and Canada, 5,7 where patients are more traceable.…”
Section: Discussioncontrasting
confidence: 74%
“…Our approach of having a contracted professional service conduct HCV recipient notifications proved to be as effective in identifying deceased recipients as other lookback strategies. The percentage of patients identified as deceased (50%) is within the range of published reports 4‐9 . In those studies, 41 to 71 percent of recipients of blood components targeted for lookback were found to be dead.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, in the paediatric population, mortality is significantly less. In a US targeted lookback, 81% of adult recipients, but only 43% of paediatric recipients, had died [13]. Similarly, in a Quebec targeted lookback, 34% of children compared with 61% of adult recipients were dead at the time of notification [4].…”
Section: Discussionmentioning
confidence: 99%
“…The 11‐year retrospective review of the HCV lookback program identified no cases of transfusion‐transmitted HCV infection, a lower yield than that reported in studies conducted before the year 2000 . The majority of recipients were deceased, with fewer than one‐third in the “physician agreed to notify” category.…”
Section: Recipient Disposition On Follow‐up Of Hcv Positive Units By mentioning
confidence: 91%